Vascular smooth muscle cell-derived exosomes promote osteoblast-to-osteocyte transition via β-catenin signaling - Fernandes, Célio J.C. [UNESP]; Silva, Rodrigo A.; Ferreira, Marcel R. [UNESP]; Fuhler, Gwenny M.; Peppelenbosch, Maikel P.; van der Eerden, Bram CJ.; Zambuzzi, Willian F. [UNESP] (Elsevier, 2024)
Blood vessel growth and osteogenesis in the skeletal system are coupled; however, fundamental aspects of vascular function in osteoblast-to-osteocyte transition remain unclear. Our study demonstrates that vascular smooth muscle cells (VSMCs), but not endothelial cells, are sufficient to drive bone marrow mesenchymal stromal cell-derived osteoblast-to-osteocyte transition via β-catenin signaling and exosome-mediated communication. We found that VSMC-derived exosomes are loaded with transcripts encoding proteins associated with the osteocyte phenotype and members of the WNT/β-catenin signaling pathway. In contrast, endothelial cell-derived exosomes facilitated mature osteoblast differentiation by reprogramming the TGFB1 gene family and osteogenic transcription factors osterix (SP7) and RUNX2. Notably, VSMCs express significant levels of tetraspanins (CD9, CD63, and CD81) and drive the intracellular trafficking of exosomes with a lower membrane zeta potential than those from other cells. Additionally, the high ATP content within these exosomes supports mineralization mechanisms, as ATP is a substrate for alkaline phosphatase. Osteocyte function was further validated by RNA sequencing, revealing activity in genes related to intermittent mineralization and sonic hedgehog signaling, alongside a significant increase in TNFSF11 levels. Our findings unveil a novel role of VSMCs in promoting osteoblast-to-osteocyte transition, thus offering new insights into bone biology and homeostasis, as well as in bone-related diseases. Clinically, these insights could pave the way for innovative therapeutic strategies targeting VSMC-derived exosome pathways to treat bone-related disorders such as osteoporosis. By manipulating these signaling pathways, it may be possible to enhance bone regeneration and improve skeletal health in patients with compromised bone structure and function.